Capeverdean reflexives: the importance of a silent Voice - Pratas, Fernanda (2018)
In Capeverdean, a Portuguese-based Creole language, many reflexive contexts do not show any overt reflexive expression. This is the case of transitive verbs like bisti ‘dress’ in simple clauses: Ana bisti ‘Ana has dressed herself’. This is a perplexing fact, given that there is an anaphor of the SELF-type available in the language: (si) kabesa — literally ‘his/her head’ —, meaning ‘himself/ herself’, which participates in reflexive clauses with other verbs. The current paper explores this puzzle, ending with a proposal supported empirically and also by recent studies for other languages. This novel analysis goes as follows: all Capeverdean finite sentences, except unaccusatives, have a Voice head, responsible for assigning external theta-roles. This also includes middles, passives and this type of reflexives. It is this Voice head that, in spite of being silent, attracts the internal argument to a preverbal position and provides the interpretation for an implicit external argument, which is syntactically active.